Analysis Of Medical Services Distribution And Nurse Relationship In Policy Making On Nurse Performance At Royal Prima Hospital Medan 2021 - Al Annissa Fadhila Ainy; Rima Pertiwi Br. Sembiring; Chrismis Novalinda Ginting; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
Performance is an obligation that must be improved by every nurse, good performance can increase patient satisfaction at the hospital, the way that must be done by the hospital in improving performance is by distributing medical services in accordance with the provisions in the hospital. This study aims to analyze the distribution of medical services and the relationship of nurses in policy making on nurse performance. This study uses two approaches, namely qualitative and quantitative. The population in this study were nurses at the Royal Prima General Hospital in Medan, amounting to 386 nurses, the sample used in this study was 224 nurses. This study uses two statistical applications for processing research data, namely SPSS and LISLER. The results of his research from the two approaches in this study state that the variables of the principle of fairness, the principle of fairness, the principle of transparency, and the principle of consistency affect the performance of nurses, while the relationship between nurses in decision making does not affect the performance of nurses at the Royal Prima General Hospital Medan in 2021.